Identification of the phase composition of solid microparticles in the nasal mucosa of patients with chronic hypertrophic rhinitis using Raman microspectroscopy - Kristina Čabanová (Nature Portfolio, 2021)
Abstract Solid particles, predominantly in micron and submicron sizes, have repeatedly been observed as a threat to a human health unique compared to the other textures of the same materials. In this work, the hypothesis the solid metal-based particles play a role in the pathogenesis of chronic hypertrophic rhinitis was investigated in patients who had not responded positively to medication. In the group of 40 randomly selected patients indicated for surgical mucotomy, the presence of solid micro- and submicron particles present in their nasal mucosa was assessed. For comparison, a set of 13 reference samples from patients without diagnosed chronic hypertrophic rhinitis was evaluated. The analysis was performed using Raman microspectroscopy. The advantage of this method is the direct identification of compounds. The main detected compounds in the mucosa samples of patients with chronic hypertrophic rhinitis were TiO2, carbon-based compounds, CaCO3, Ca(Fe, Mg, Mn)(CO3)2 MgCO3, Fe2O3, BaSO4, FeCO3 and compounds of Al and Si, all of which may pose a health risk to a living organism. In the reference samples, only TiO2 and amorphous carbon were found. In the control group mucosa, a significantly lower presence of most of the assessed compounds was found despite the longer time they had to accumulate them due to their higher mean age. Identification and characterisation of such chemicals compounds in a living organism could contribute to the overall picture of the health of the individual and lead to a better understanding of the possible causes not only in the chronic hypertrophic rhinitis, but also in other mucosal and idiopathic diseases.